Development of Infographic Poster Media in the Pancasila Education Subject for High School - Hartatik, Sri; Pebriantika, Leni; Susila, Heni Rita (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop infographic poster media for the Pancasila Education subject in Grade XI senior high school and to evaluate its feasibility as an instructional medium. The study employed a Research and Development (R&D) approach using the Dick and Carey model, combined with Tessmer’s formative evaluation. The development process included needs analysis, instructional design, product development, and iterative evaluation through expert validation and student testing. The subjects consisted of three experts (content, instructional design, and media) and students involved in one-to-one, small group, and field-testing stages. The results indicate that the developed infographic poster media is highly feasible, with validation scores of 87.38% from the content expert, 85.50% from the instructional design expert, and 84.67% from the media expert. Student evaluations also showed very high acceptance, with scores of 88.39% in one-to-one evaluation and 90.51% in small group evaluation. The findings demonstrate that infographic posters effectively present complex and abstract concepts in a concise, structured, and visually engaging manner. Infographic poster media can serve as an innovative and effective instructional tool to enhance student engagement, comprehension, and independent learning in Pancasila Education.